1983
DOI: 10.1002/cne.902160302
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cytoarchitectonic study of gudden's tegmental nuclei in some mammals

Abstract: The structure and location of the dorsal and ventral tegmental nuclei of Gudden were studied in brains of 12 species of mammals. The ventral tegmental nucleus of Gudden is composed of oval or polygonal, medium-sized, well-stained cells, and includes the pars principalis situated ventral to the fasciculus longitudinalis medialis, and the pars suprafascicularis in the central gray matter dorsal to the fasciculus longitudinalis medialis (in the golden hamster, mouse, vole, and house shrew). The dorsal tegmental n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 16 publications
1
20
1
Order By: Relevance
“…As mentioned above, some authors have regarded the NIc as a caudal extension of the dorsal raphé nucleus (Taber, 1961;Hayakawa and Zyo, 1983). Our PHA-L evidence indicates that its projection pattern is very distinct from that arising in the NIc (compare Figs.…”
Section: Neuronal Outputs Of the Pontine Periventricular Extension Ofmentioning
confidence: 65%
See 2 more Smart Citations
“…As mentioned above, some authors have regarded the NIc as a caudal extension of the dorsal raphé nucleus (Taber, 1961;Hayakawa and Zyo, 1983). Our PHA-L evidence indicates that its projection pattern is very distinct from that arising in the NIc (compare Figs.…”
Section: Neuronal Outputs Of the Pontine Periventricular Extension Ofmentioning
confidence: 65%
“…As noted above, some authors regard the NIc as a caudal extension of the dorsal raphé nucleus (Taber, 1961;Hayakawa and Zyo, 1983). Therefore, it is important here to provide a comparison between projections of the NIc and what we regard as the caudal dorsal raphé nucleus.…”
Section: Neuronal Projections From the Nimentioning
confidence: 95%
See 1 more Smart Citation
“…As is well known, cholinergic sleep systems, both ascending and descending, extend across this entire anterior limbic territory (limbic cholinergic system). Petrovický (Petrovický, 1971(Petrovický, , 1973(Petrovický, , 1985a and others (Hayakawa and Zyo, 1983;Irle et al, 1984) have precisely identified the cytoarchitecture and connections of Fig. 3.…”
Section: Johann Bernhard Alois Von Gudden's Nucleimentioning
confidence: 95%
“…Histology, Histochemistry, Fiber Connections Stephan (1961, 1966b, SEP, Crocidura) Bauchot (1963, DIE, Crocidura) Girod (1976, HYP, Suncus) Hayakawa and Zyo (1983, tegmentum, Suncus) Hayakawa and Zyo (1984, tegmen to-mammillar connections, Suncus) Isomura et a1. (1986 Mohanty and Kar (1982, biochemistry, Suncus) Naik and Dominic (1971, HYP, Suncus) Rehkamper (1981, NEO, Crocidura) Schwerdtfeger (1984, HIP, Crocidura) Sigmund et a1.…”
Section: Cell and Area Measurementsmentioning
confidence: 98%